Evaluating the performance of conventional DAF and PosiDAF processes for cyanobacteria separation at a pilot plant scale. Issue 2 (9th May 2022) - Yap, R. K. L.; Rao, N. R. H.; Holmes, M.; Whittaker, M.; Stuetz, R. M.; Jefferson, B.; Bulmuş, V.; Peirson, W. L.; Henderson, R. K.
Abstract: In this work, a commercially available water treatment polymer poly( N, N -diallyl- N, N -dimethylammonium chloride) (PDADMAC) and a hydrophobically modified polymer (HMP) designed to adhere to bubble surfaces were applied for the first time in the novel Posi-dissolved air flotation process (PosiDAF) that uses polymer-modified bubbles, at pilot-scale for the treatment of waste stabilisation pond samples rich in algae. It was found that PDADMAC in PosiDAF gave comparable removal to that achieved using conventional DAF at >95% cell separation. Furthermore, the float layer was more uniform and thicker with up to 8% solid contents compared to conventional DAF, which comprised discrete floc clusters with an average solid concentration of ∼4.1%. In contrast to the use of PDADMAC, the application of the HMP did not achieve similarly good separation at pilot scale. It was hypothesised that this may be due to the micellisation of the HMP on the bubble surface, creating unstable bubbles that coalesced and prevented polymer–bubble–cell interactions, which are crucial for effective cell separation. On comparison of the costs of PosiDAF and conventional DAF, it was found that PosiDAF resulted in cost-savings of up to 74% due to low chemical consumption. In summary, PosiDAF reduced chemical cost and increased solid contents in the metal-free float. HIGHLIGHTS: Effective translation of PosiDAF from laboratory to pilot-scale is achieved. PosiDAF float layer is structurally coherent compared to the conventional DAF float layer. Compared to conventional DAF, PosiDAF can reduce 74% costs due to low chemical use. Graphical Abstract